Diminazene aceturate: an antibacterial agent for Shiga-toxin-producing Escherichia coli O157:H7 - Wu SY; Park GY; Kim SH; Hulme J; An SSA (Dove Medical Press, 2016)
Si-Ying Wu,1 Gil-Yong Park,1 So-Hee Kim,2 John Hulme,1 Seong Soo A An1 1Department of BioNano Technology, Gachon BioNano Research Institute, Gachon University, Seongnam-si, 2Seoul National University Bundang Hospital, Gyeonggi-do, Republic of Korea Abstract: The aim of this study was to investigate the bacteriostatic and bactericidal effects of diminazene aceturate (DA) against five strains of pathogenic bacteria and two strains of nonpathogenic bacteria. The results showed that 5 µg/mL of DA suppressed the growth of pathogenic Escherichia coli by as much as 77% compared with the controls. Enterohemorrhagic E. coli EDL933 (an E. coli O157:H7 strain) was the most sensitive to DA with a minimum inhibitory concentration of 20 µg/mL. Additional investigations showed that DA induced the highest level of intracellular reactive oxygen species in EDL933. A positive correlation between the reactive oxygen species levels and DA concentration was demonstrated. DA (5 µg/mL) was also a potent uncoupler, inducing a stationary phase collapse (70%–75%) in both strains of E. coli O157:H7. Further investigation showed that the collapse was due to the NaCl:DA ratio in the broth and was potassium ion dependent. A protease screening assay was conducted to elucidate the underlying mechanism. It was found that at neutral pH, the hydrolysis of H-Asp-pNA increased by a factor of 2–3 in the presence of DA, implying that DA causes dysregulation of the proton motive force and a decrease in cellular pH. Finally, a commercial verotoxin test showed that DA did not significantly increase toxin production in EDL933 and was a suitable antibacterial agent for Shiga-toxin-producing E. coli. Keywords: E. coli O157, Berenil©, ROS, reversible, protease, enterohemorrhagic